Linearly elastic constitutive relations and consistency for GBT-based thin-walled beams. (July 2015) - de Miranda, Stefano; Gutierrez, Alejandro; Melchionda, Domenico; Patruno, Luca
Abstract: The present paper focuses on the constitutive assumptions, both for the isotropic and orthotropic cases, and consistency in the framework of the Generalized Beam Theory. In particular, a novel approach based on energetic arguments, able to automatically select appropriate constitutive relations in accordance with the GBT kinematics, is presented. Furthermore, the concept of consistency of a GBT-based model is established and a consistency analysis is presented. This yields a formal rational basis to investigate the effects of the various families of cross-section deformation modes in terms of predictive capabilities of the GBT model. Some numerical examples illustrate the arguments exposed in the paper. Abstract : Highlights: A new approach for the determination of appropriate constitutive relations in the GBT framework is proposed. The concept of consistency of a GBT-based model is established and a consistency analysis is presented. Numerical examples show the importance of the arguments discussed, especially if orthotropic materials are considered.